2022
DOI: 10.3390/diagnostics12102500
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of 18F-Fluorodeoxyglucose PET Image Quality by Deep-Learning-Based Image Reconstruction Using Advanced Intelligent Clear-IQ Engine in Semiconductor-Based PET/CT Scanners

Abstract: Deep learning (DL) image quality improvement has been studied for application to 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT). It is unclear, however, whether DL can increase the quality of images obtained with semiconductor-based PET/CT scanners. This study aimed to compare the quality of semiconductor-based PET/CT scanner images obtained by DL-based technology and conventional OSEM image with Gaussian postfilter. For DL-based data processing implementation, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Our results showed that the DL denoising technique can maintain or improve the diagnostic image quality of low [ 18 F]FDG PET in patients with lymphoma. These results were consistent with the finding of previous studies ( 21 , 28 ). Furthermore, the quantitative consistency of SUV between LD PET with DL denoising and RD PET was demonstrated in a larger population.…”
Section: Discussionsupporting
confidence: 94%
“…Our results showed that the DL denoising technique can maintain or improve the diagnostic image quality of low [ 18 F]FDG PET in patients with lymphoma. These results were consistent with the finding of previous studies ( 21 , 28 ). Furthermore, the quantitative consistency of SUV between LD PET with DL denoising and RD PET was demonstrated in a larger population.…”
Section: Discussionsupporting
confidence: 94%